High-quality genome sequence and description of Chryseobacterium senegalense sp. nov. (March 2016) - Lo, C.I.; Sankar, S.A.; Mediannikov, O.; Ehounoud, C.B.; Labas, N.; Faye, N.; Raoult, D.; Fournier, P.-E.; Fenollar, F.
Abstract: Strain FF12 T was isolated from the mouth of a West African lungfish ( Protopterus annectens ) in Senegal. MALDI-TOF-MS did not provide any identification. This strain exhibited a 97.97% 16S rRNA sequence identity with Kaistella flava . Using a polyphasic study including phenotypic and genomic analyses, strain FF12 T is Gram-negative, aero-anaerobic, oxidase-positive, non-motile, non-spore-forming, and exhibited a genome of 4, 397, 629 bp with a G+C content of 35.1% that coded 4, 001 protein-coding and 55 RNA genes. On the basis of these data, we propose the creation of Chryseobacterium senegalense strain FF12 T .